2013
DOI: 10.1089/ten.tea.2012.0724
|View full text |Cite
|
Sign up to set email alerts
|

Recombinant Human Bone Morphogenetic Protein-2 Stimulates the Osteogenic Potential of the Schneiderian Membrane: A Histometric Analysis in Rabbits

Abstract: This study evaluated the osteoinductive effect of the recombinant human bone morphogenetic protein-2 (rhBMP-2)-coated biphasic calcium phosphate (BCP) carrier system on the grafted sinus area, including surrounding tissues and the Schneiderian membrane. A total of 18 male rabbits were used in this study; two for in vitro and 16 for in vivo experiments. Schneiderian membranes taken from two animals were cultured with or without rhBMP-2, and quantitative reverse transcriptase-polymerase chain reaction analysis w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
43
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 27 publications
(54 citation statements)
references
References 34 publications
8
43
3
Order By: Relevance
“…When an implant is placed, new bone formation appears to start from the original cortical bone of the sinus wall and to progress towards the center in the apical direction [9]. Newly formed cortical bone could play a similar role to the original cortical bone.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…When an implant is placed, new bone formation appears to start from the original cortical bone of the sinus wall and to progress towards the center in the apical direction [9]. Newly formed cortical bone could play a similar role to the original cortical bone.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the development of bone substitute to promote bone regeneration and osseointegration has made the procedure more predictable, and has extended the applicability of the 1-stage approach [8]. Furthermore, many attempts have been made to use growth factors (e.g., bone morphogenetic protein), which are known to induce rapid bone formation in the maxillary sinus [9].…”
Section: Introductionmentioning
confidence: 99%
“…Bioactivity of BCP could be enhanced by rhBMP-2. Choi et al compared the bone formation effect of rhBMP-2-coated BCP with pure BCP on a grafted sinus area in rabbits [29]. A significant increase in the expression of RUNX2, type I collagen, alkaline phosphatase and osteopontin was observed in both groups.…”
Section: Discussionmentioning
confidence: 99%
“…In previous studies, oxysterol induced in vivo osteogenesis like bone morphogenetic protein-2 (BMP-2), or synergistically increased the osteoinductive effects of BMP-2 [30,37,38]. Since complications of BMP-2 application have emerged in research and clinical fields [39,40], oxysterol has received attention as a substitute or regulating factor for BMP-2. Our previous study also showed an increase in alkaline phosphatase with oxysterol surface coating, and simultaneous apatite and oxysterol coating could synergistically enhance in vitro osteogenesis [27].…”
Section: Discussionmentioning
confidence: 99%